Antiviral Activity of Lovastatin against Respiratory Syncytial Virus In Vivo and In Vitro - Gower, Tara L. (American Society for Microbiology, 2001)
Respiratory syncytial virus (RSV) is an important human pathogen that can cause severe and life-threatening respiratory infections in infants and immunocompromised adults. We have recently shown that the RSV F glycoprotein, which mediates viral fusion, binds to RhoA. One of the steps in RhoA activation involves isoprenylation at the carboxy terminus of the protein by geranylgeranyltransferase. This modification allows RhoA to be attached to phosphatidyl serine on the inner leaflet of the plasma membrane. Treatment of mice with lovastatin, a drug that inhibits prenylation pathways in the cell by directly inhibiting hydroxymethylglutaryl coenzyme A reductase, diminishes RSV but not vaccinia virus replication when administered up to 24 h after RSV infection and decreases virus-induced weight loss and illness in mice. The inhibition of replication is not likely due to the inhibition of cholesterol biosynthesis, since gemfibrozil, another cholesterol-lowering agent, did not affect virus replication and serum cholesterol levels were not significantly lowered by lovastatin within the time frame of the experiment. Lovastatin also reduces cell-to-cell fusion in cell culture and eliminates RSV replication in HEp-2 cells. These data indicate that lovastatin, more specific isoprenylation inhibitors, or other pharmacological approaches for preventing RhoA membrane localization should be considered for evaluation as a preventive antiviral therapy for selected groups of patients at high risk for severe RSV disease, such as the institutionalized elderly and bone marrow or lung transplant recipients.